Green Investment Strategies and Financial Performance: Evidence from Portuguese Firms - Pedro Alçada e Silva (Notas Económicas)
This study analyzes how environmental investment strategies affect the financial performance of Portuguese companies. The analysis uses company-level data from the Extractive and Manufacturing Industries and Electricity, Gas and Water Production and Distribution Sectors for the period between 2010 and 2021. The empirical analysis showed that there is no statistically significant relationship between the level of green investment and the financial performance of the companies under study. It was also possible to ascertain that eco-innovations have a positive relationship with the level of green investment, with the adoption of certain types of green innovation strategies having a greater impact on both environmental investment and financial performance.